Cyber attack mitigation for cyber–physical systems: hybrid system approach to controller design. Issue 7 (1st April 2016) - Kwon, Cheolhyeon; Hwang, Inseok
Abstract : This study considers robust controller design for cyber–physical systems (CPSs) subject to cyber attacks. While previous studies have investigated secure control by assuming specific attack strategies, in this study the authors propose a robust hybrid control scheme containing multiple sub‐controllers, each matched to a different type of cyber attack. A system using this control scheme is able to adapt its behaviour to various cyber attacks (including those which have not been specifically addressed in the sub‐controller designs) by switching sub‐controllers to achieve the best performance. They propose a method for designing the secure switching logic to counter possible cyber attacks and to mathematically verify the system's performance and stability as well. The performance of the proposed control scheme is demonstrated by the hybrid H 2 – H ∞ controller applied to a CPS subject to cyber attacks.